2003
DOI: 10.1002/cne.10610
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Reelin causes malpositioning of nigral dopaminergic neurons: Evidence from comparison of normal and Relnrl mutant mice

Abstract: The reeler gene (Reln(rl), formerly rl) product Reelin controls neuronal migration and positioning and thereby plays a key role in brain development. Mutation of Reln leads to widespread disruption of laminar cortical regions and ectopia in some brainstem nuclei. In the embryonic striatum of normal mice, a substantial expression of reelin mRNA has been documented; however, the anomalous positioning of neurons in the basal ganglia of reeler mice remains to be studied. We provide first evidence for a potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 63 publications
3
68
0
2
Order By: Relevance
“…Previous studies proposed that the SN does not form in Reeler mutants (Kang et al, 2010;Nishikawa et al, 2003). We show here that in Reeler as well as in Dab1 KO and Apoer2/Vldlr double KO mutants, the lack of lateral dispersion of SN neurons is confined to intermediate levels, whereas the anterior SN is merely disorganized (see also Sharaf et al, 2013).…”
Section: Reelin Regulates Tangential Migration Of Da Neuronssupporting
confidence: 65%
See 2 more Smart Citations
“…Previous studies proposed that the SN does not form in Reeler mutants (Kang et al, 2010;Nishikawa et al, 2003). We show here that in Reeler as well as in Dab1 KO and Apoer2/Vldlr double KO mutants, the lack of lateral dispersion of SN neurons is confined to intermediate levels, whereas the anterior SN is merely disorganized (see also Sharaf et al, 2013).…”
Section: Reelin Regulates Tangential Migration Of Da Neuronssupporting
confidence: 65%
“…The reelin pathway could play a role in regulating tangential migration of DA neurons, as it has been reported that the SN does not form in Reeler mutants (Kang et al, 2010;Nishikawa et al, 2003;Trommsdorff et al, 1999). Reelin, a large extracellular glycoprotein, regulates migration in several brain areas and signals via the transmembrane receptors APOER2 (APOE receptor 2; LRP8 -Mouse Genome Informatics) and VLDLR (very low density lipoprotein receptor) and the downstream effector DAB1 (disabled 1) (D'Arcangelo et al, 1999;Rice et al, 1998).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Thus the timing for striatal dysplasia occurs much later than the deficiency in SN formation. Third, reelin has been reported to be produced in the striatum and transported to the SN (Nishikawa et al, 2003). We found that reelin expression was not altered in either the striatum or the SN…”
Section: A Biological Function For Layer Iii-specific Gene Ebf1mentioning
confidence: 59%
“…Whereas pharmacological inhibition or deletion of Cxcr4 does not affect the number of mDA neurons, it affects their migration, as some cells remain in the IZ and do not reach the MZ (Yang et al, 2013b). Tangential migration of mDA neurons is regulated by the neural L1 cell adhesion molecule (L1CAM) (Demyanenko et al, 2001;Ohyama et al, 1998) and RELN (reelin) (Kang et al, 2010;Nishikawa et al, 2003). Mice lacking Reln or the cytoplasmic adaptor protein Dab1 (disabled 1) have fewer PSA-NCAM + tangential fibers and fewer mDA neurons reaching the SNc, despite normal numbers of mDA neurons being generated (Kang et al, 2010).…”
Section: Migration Of Postmitotic Mda Neuroblasts and Neuronsmentioning
confidence: 99%